Epidemiology of Oestrus ovis (Diptera: Oestridae) in sheep in Botucatu, State of São Paulo - Silva,Bruna Fernanda da (2012)
The seasonal factors that influence Oestrus ovis infestation in sheep were determined in Botucatu, State of São Paulo, Southwestern Brazil, from April 2008 to March 2011. Two tracer lambs were monthly exposed to natural infestation by O. ovis larvae for 28 consecutive days, by grazing with a sheep flock. Tracer animals were then euthanized and the larvae of O. ovis recovered from nasal and sinus cavities. Of the 72 tracer lambs, 50% were infested with O. ovis larvae and the mean intensity of infestation per head infested was 16.8 larvae, with an average of 7.8 L1, 5.3 L2 and 3.7 L3. O. ovis larvae were present during the four seasons of the year, but the mean larval burden was significantly higher during the spring and summer months, compared to winter (P < 0.05). The highest rate of larvae recovery coincided with mean temperatures between 20 °C and 25 °C and air relative humidity around 70%. Results suggest that evolution and development of O. ovis practically occurs throughout the entire year, with larval infestation especially frequent during the spring and summer months.